2012
DOI: 10.5120/8398-2001
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach on Rare Association Rule Mining

Abstract: Association rule mining is the process of finding some relations among the attributes/attribute values of huge database based on support value. Most existing association mining techniques are developed to generate frequent rules based on frequent itemsets generated on market basket datasets. A common property of these techniques is that they extract frequent itemsets and prune the infrequent itemsets. However, such infrequent or rare itemsets and consequently the rare rules may provide valuable information. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The measure of Comprehensibility determines the significance of a rule based on the number of items presented in both the antecedent and consequent domains (Aher & Lobo, 2013; Hoque et al ., 2012; Sikka et al ., 2012), which can be represented as:ComprehensibilityAB=log1+Blog1+AB…”
Section: Association Rule Discovery and Generation In Adaptive Micro mentioning
confidence: 99%
See 1 more Smart Citation
“…The measure of Comprehensibility determines the significance of a rule based on the number of items presented in both the antecedent and consequent domains (Aher & Lobo, 2013; Hoque et al ., 2012; Sikka et al ., 2012), which can be represented as:ComprehensibilityAB=log1+Blog1+AB…”
Section: Association Rule Discovery and Generation In Adaptive Micro mentioning
confidence: 99%
“…Particularly, in micro open learning, instructors or the service‐oriented system (eg, MLaaS) is responsible for identifying the students potentially at risk. This minority normally requires extra assistance or instructors’ intervention (Hoque, Nath, & Bhattacharyya, 2012). The value of minimum Support is set too high or too low can cause omission or combinatorial explosion of rules (Kiran & Reddy, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As the most important purpose of rule mining is to find some hidden information, it should extract those rules that have comparatively less occurrence in the database. The following expression can be used to quantify the interestingness [8, 9, 14, 15]: Interestingness(XY)=SUP(XY)SUP(X)×SUP(XY)SUP(Y)×(1SUP(XY)|D|), where | D | indicates the total number of transactions in the database. …”
Section: Preliminariesmentioning
confidence: 99%
“…Qodmanan et al applied MOGA to association rule mining without taking the minimum support and confidence into account by applying the FP-tree algorithm [9]. Hoque et al presented a method to generate both frequent and rare itemsets using multiobjective genetic algorithm [14]. Fung et al suggested a novel MOGA based rule mining method for affective product design, which can discover a set of rules relating design attributes with customer evaluation based on survey data [44].…”
Section: Preliminariesmentioning
confidence: 99%
“…There is less research on subjective interestingness and it is relatively immature. Hoque et al and Zhang et al presented methods to generate both frequent and rare itemsets using multiobjective genetic algorithm [10,11]. How to mine the real and effective association rules reflecting interests of users is the common goal for researchers.…”
Section: Introductionmentioning
confidence: 99%